Social Behavior of Local Sheep in Semi-Intensive Rearing System - Imam Munandar (Journal of Tropical Animal Science and Technology, 2022)
Sheep is a livestock commodity that is used to fulfill national meat needs. This study aims to examine the social behavior of local sheep reared in semi-intensive rearing systems and different types of concentrates. This study used 20 sheep with an average of 16.51 kg. The experiment was conducted in a completely randomized design with a factorial pattern. The first factor is the rearing system and the second factor is the type of concentrate feed. Parameters observed are vocalization, rest and social play. Data were analyzed using analysis of variance (ANOVA) and t-test. The results showed that the type of concentrate and maintenance system did not affect social behavior (vocalization, rest and play).